Effect of doxorubicin on cardiac lipid metabolism-related transcriptome and the protective activity of Alda-1 - Menezes Souza, Leonardo da Cunha [UNESP]; Fernandes, Fabio Henrique [UNESP]; Presti, Paula Torres [UNESP]; Anjos Ferreira, Ana Lucia [UNESP]; Favero Salvadori, Daisy Maria [UNESP] (Elsevier B.V., 2021)
The use of doxorubicin (DOX) as an antineoplastic drug is compromised by its cardiotoxicity risk. Although several mechanisms have been proposed for DOX-induced cardiac dysfunction, there is still increased interest in assessing its effects. Likewise, it is important to find protocols that can prevent or minimize the side effects of DOX without hindering its antitumor activity. Thus, this study was designed to investigate the molecular mechanisms underlying DOX cardiotoxicity, with a special focus on cardiac energy metabolism and the ability of Alda-1 (ALDH2 agonist) to prevent DOX-induced cardiac alterations. We explored the effects of DOX on the histological morphology of the myocardium, on lipid profile, and on the expression of genes related to fatty acid metabolism, in the presence and absence of Alda-1 (8 mg/kg body weight; b.wt.). Two DOX treatment protocols were used: a single dose of DOX (4 mg/kg b.wt.); four doses of DOX (4 mg/kg b.wt.), one dose/week, for 4 weeks. Treatment with DOX caused a progressive injury in the cardiac tissue and an increase in the blood total cholesterol, high-density lipoproteins, very low-density lipoproteins and triglyceride, as well as an up-regulation of FABP4 (DOX and DOX + Alda-1 groups) and Slc27a2 (in DOX-treated animals). Alda-1 administration promoted reduction in the severity of the histopathological injuries (after single dose of DOX) and Slc27a2 overexpression was restored. In conclusion, the study revealed novel insights regarding the development of DOX-mediated cardiomyopathy, indicating a relationship between DOX exposure and FABP4 and Slc27a2 overexpression, and confirmed the cardioprotective effect of Alda-1.
Keywords: Cardiotoxicity; Cardioprotection; ALDH2 activator; Fatty acid binding protein